(untitled) (Bangladesh Journal of Botany, 2023)
An experiment was conducted to explore the changes of germination rate, protein and vitamin C content in the seeds and the chlorophyll content of the seedlings under different irradiation time and intensity. Experiments showed that plasma treatment of chicory seeds promoted the germination and biological content of bitter seeds in 100-300W, 5-15s, and the germination rate was relatively higher under 200W conditions, the content of vitamin C and protein in seeds was relatively higher under 300W conditions. Bangladesh J. Bot. 52(2): 445-450, 2023 (June) Special